Determinants of gout therapy non-adherence in patients attending an Egyptian rheumatology outpatient clinic - Samira Saad Ali; Samah Ramadan Shaheen Ibrahim; Manal Saeed Mohammed (BMC Nursing, 2026)
Abstract Background Non-adherence to urate-lowering therapy (ULT) is a significant issue in the management of gout, a prevalent form of inflammatory arthritis that adversely affects patients’ quality of life and burdens healthcare systems. Although ULT is effective in reducing serum uric acid levels, many patients fail to adhere to their medication regimens. Factors contributing to this non-adherence include treatment complexity, medication costs, side effects, forgetfulness, and individual health beliefs, as well as issues related to healthcare providers such as communication and education. Understanding these barriers is crucial for developing effective nursing interventions that enhance adherence and improve patient outcomes. Aim Identify and analyze the factors influencing patient adherence to gout therapy and explore the barriers experienced by patients in a clinical setting. Methods A descriptive research design was utilized with a convenience sample of 150 adults aged 21–60 years diagnosed with gout, who had been prescribed urate-lowering therapy for at least three months. Data collection occurred from November 1, 2024, to March 30, 2025. Participants were required to have the capacity to provide informed consent and understand the study requirements. Individuals with comorbidities affecting medication adherence, those currently enrolled in other clinical trials, and individuals unable to provide informed consent were excluded from the study. The study employed two questionnaires: a sociodemographic and clinical data questionnaire to gather relevant participant information and Intentional Non-Adherence Scale (INAS) to assess medication adherence. Results: Approximately 60.7% of respondents indicate a low adherence level to medications, while 39.3% report a high adherence level to medications. Key factors affecting adherence include socio-demographic variables, such as higher rates among males and those aged 30–39, as well as sufficient income. In addition, the findings suggest that clinical data correlate with better adherence. Conclusion and implications This study highlights critical socio-demographic and clinical characteristics of gout patients, emphasizing the need for enhanced public awareness campaigns, early screening programs, and targeted interventions to improve healthcare access and medication adherence among underserved populations. By addressing barriers such as medication costs and psychological factors through tailored nursing interventions and multidisciplinary collaboration, we can significantly enhance patient outcomes and quality of life for individuals living with gout.